Fear of heights shapes postural responses to vibration-induced balance perturbation at virtual height - Bzdúšková, Diana; Marko, Martin; Hirjaková, Zuzana; Riečanský, Igor; Kimijanová, Jana (Frontiers in Human Neuroscience, 2023)
Standing upright at height is a challenging situation involving intense threat of balance loss and fall. The ability to maintain balance in such conditions requires properly resolving sensory conflicts and is influenced by fear. To get more insight on the role of fear in balance control at height, we explored the dynamics of postural behaviour in the situation of enhanced threat of potential balance loss. In 40 young individuals with varying fear of heights, we combined simulated exposure to height in a virtual reality environment with bilateral vibration of tibialis anterior muscles which evokes posture destabilisation (the so-called vibration-induced falling). Under such condition of enhanced postural threat, individuals with intense fear of heights showed stronger stiffening of posture compared with individuals with low fear of heights who react more flexibly and adaptively to posture destabilisation. This group difference was evident already at ground level but further increased during virtual height exposure. Our data show that fear of height significantly affects posture adaptation to balance-destabilizing events. Our findings demonstrate that the assessment of postural behaviour during threatening situations in a virtual reality environment provides valuable